Influence of agronomic practices on the photosynthetic activity of grain sorghum hybrids in the Northern Steppe of Ukraine - D. Sukhina; N. Novytska (Наукові доповіді Національного університету біоресурсів і природокористування України)
The study of the photosynthetic activity of grain sorghum is crucial for enhancing its productivity under the conditions of the Northern Steppe of Ukraine, characterised by unstable moisture levels and significant temperature fluctuations. This research aimed to determine the influence of hybrids, plant density, and the application of the plant growth regulator Appetaizer on the indicators of photosynthetic activity in grain sorghum. The research was conducted over the period 2022-2024 on experimental plots in the Dnipropetrovsk Region. Winter wheat served as the preceding crop, and cultivation practices followed the standard techniques for the region (except for the investigated elements and a row spacing of 45 cm). The methods employed included: field observations of the phenological phases of growth and development of the crop, as well as the impact of the studied factors on the photosynthetic activity of grain sorghum; tabular methods for the systematisation, arrangement, and presentation of the data obtained; and graphical methods for data visualisation. The study established that, in terms of photosynthetic potential, the optimal combinations were found to be: the hybrid ES Alize at a density of 170 thousand plants/ha with the application of the plant growth regulator (PGR) (392.7 thousand m2/ha*days); hybrids ES Alize and ES Foehn at a density of 200 thousand plants/ha under control conditions (407.2 and 398.4 thousand m2/ha*days respectively); the ES Foehn hybrid at the same density with the application of the PGR (404.0 thousand m2/ha*days); and hybrids ES Alize and ES Foehn at a density of 230 thousand plants/ha under control conditions (400.0 and 415.7 thousand m2/ha*days respectively), as well as ES Alize with the application of the PGR (403.2 thousand m2/ha*days), demonstrated optimal results. In terms of net photosynthetic productivity, the best results were recorded for the Albanus hybrid at a density of 170 thousand plants/ha – both without PGR (4.67 g/m2 per day) and with PGR (4.70 g/m2 per day); for the Albanus (4.77) and ES Monsoon (5.07) hybrids at 200 thousand plants/ha under control conditions, as well as with PGR (4.89 and 5.12 g/m2 per day, respectively); and at 230 thousand plants/ha – for the Albanus (4.78) and ES Monsoon (4.69) hybrids under control conditions, and with PGR (4.78 and 4.82 g/m2 per day, respectively). Thus, the photosynthetic activity of sorghum was influenced by plant density, hybrid, and the effect of the studied growth regulator. The results obtained will enable agricultural producers to select optimal combinations of plant density, sorghum hybrids, and the appropriateness of using growth regulators to enhance the photosynthetic activity and yield of crops